0676 Long-term Effects Of Upper Airway Stimulation For Treatment Of Obstructive Sleep Apnea On Measurements Of Central And Mixed Apneas. (27th May 2020) - Myers, S A; Sundar, K M; Strollo, P J
Abstract: Introduction: Upper airway stimulation (UAS) of the hypoglossal nerve for obstructive sleep apnea (OSA) is well-tolerated and results in sustained reduction in the apnea-hypopnea index (AHI). Treatment-emergent CSA is reported to occur in 3.5-19.8% of OSA patients treated with CPAP. We aimed to examine the occurrence or emergence of central and mixed apneas in a cohort of participants that received UAS and were followed for 5 years post implantation. Methods: The Stimulation Trial for Apnea Reduction (STAR) was a Phase III trial evaluating the safety and efficacy of UAS for CPAP-intolerant OSA. Major inclusion criteria were CPAP intolerance, AHI between 20-50, less than 25% central and mixed apneas and BMI <= 32. Polysomnography was performed at baseline, 12, 18, 36 and 60-month follow-up. Data were scored by a core lab and was then retrospectively analyzed via the STAR PSG database to measure the evolution of central and mixed apneas on UAS therapy. Results: Baseline age was 54.5 ± 10.2 years, BMI was 28.4 ± 2.6 kg/m 2 and 83% male (n=126). AHI data were non-normally distributed. Median AHI was 29.3/hr at baseline, that was reduced to 9/hr at 12-months and 6/hr at 60-months. Median central apnea index (CAI) was 0.8/hr at baseline, 0.4/hr at 12-months, and 0.2/hr at 60-months. Median mixed apnea index (MAI) was 0.2/hr at baseline, 0.7/hr at 12-months and 0.4/hr at 60-months. The 12- and 60-month CAI was significantly lower than baseline (p<0.05), but MAI was not. The percentage of central and mixed events remained stable throughout follow-up, approximately at 5% of the total AHI. Conclusion: UAS reduced the overall AHI and results in a small but significant decrease in CAI. Given that OSA and CSA frequently co-exist, the role of UAS on reducing CSA in patients with combined OSA and CSA deserves further investigation. Support: STAR study was sponsored by Inspire Medical Systems